The Practices of Occupational Safety and Health Management in Construction Industry: Case Studies of High Rise Building Projects - Khairudin, Amir Huzaifah; Kariya, Norfarahayu (Journal of Structural Monitoring and Built Environment, 2022)
This paper presents an investigation of safety practices in occupational safety and health management at high-rise building construction projects in the Klang Valley. Three case studies were selected for data collection. Data was collected through semi-structured interviews with the safety personnel of the respective projects. The findings show that overall construction projects were implemented with safety practices such as safety inspections, safety meetings among construction personnel, education and training for workers, personal protection equipment (PPE) for construction personnel and workers, and fall protection systems. Nevertheless, several problems were encountered while implementing the safety practices, which include workers' ignorance of safety working procedures, language obstruction between workers and construction personnel, and lack of awareness among workers. Some of the suggestions given by the interviewees are to provide effective safety training, get full commitment from the top management, impose punishment or penalty on those employees who have irritated the safety regulations and rules, and keep reminding the employees to be aware of their safety as the strategies to decrease problems in safety practices.